Efektivitas Penyaluran Pupuk Bersubsidi Bagi Petani Padi di Desa Petung, Kecamatan Bangsalsari, Kabupaten Jember - Hilda Dyah Nuril Arofah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the ef ectiveness of subsidized fertilizer distribution for rice farmers in Petung Village, Bangsalsari Subdistrict, Jember Regency. Subsidized fertilizer distribution is a government program designed to support agricultural productivity and national food security. However, various challenges in its implementation may af ect the ef ectiveness of fertilizer distribution to farmers. Therefore, this study was conducted to determine the level of ef ectiveness of subsidized fertilizer distribution based on the indicators of price accuracy, quantity accuracy, and timeliness. This research employed a descriptive quantitative method. The population consisted of 460 rice farmers who were members of farmer groups in Petung Village, while 214 farmers were selected as the research sample using an appropriate sampling technique. Data were collected through questionnaires distributed to the respondents. The ef ectiveness of subsidized fertilizer distribution was analyzed based on three indicators: price accuracy, quantity accuracy, and timeliness. The results showed that the overall ef ectiveness level of subsidized fertilizer distribution in Petung Village reached an average score of 81.10%, which falls into the ef ective category. Based on the indicator analysis, quantity accuracy and timeliness were categorized as ef ective because the fertilizer allocation received by farmers generally corresponded to the requirements listed in the electronic Definitive Plan for Group Needs (e- RDKK), and fertilizer was available according to the needs of the planting season. Meanwhile, the price accuracy indicator was categorized as less ef ective because some farmers still purchased subsidized fertilizer at prices exceeding the government-established Maximum Retail Price (HET). These findings indicate that, overall, the subsidized fertilizer distribution program in Petung Village has been ef ectively implemented. However, greater supervision of subsidized fertilizer pricing, as well as stronger coordination and communication among stakeholders, are needed to ensure that the distribution process becomes more optimal and complies with existing reg
Validasi dan Finalisasi Ratna 17 Juli 2026
Keywords: efectiveness; distribution accuracy